A Discussion On The African Continental Free Trade Area And Competition - Nkomo, Charity (Department of Commercial Law, 2020)
According to Olasupo Owoeye, as the world is becoming increasingly globalized, it is difficult for some regions, for example, the African continent, to become competitive in the global market because of their overly protectionist measures1 . Former WTO Director, Pascal Lamy, also noted that Africa should no longer rely on external demand for its goods and services to support its growth but must take steps to accelerate regional integration, as it remains the least developed continent with the highest number of least developed countries in the world2 . This explains the formation of the African Continental Free Trade Area by the African Union members; whose main objective is to boost intra African trade and create a single continental market for goods and services. The African Continental Free Trade Area is expected to enhance competitiveness at both the industry and enterprise level through exploitation of opportunities for scale production, continental market access and better allocation of resources. 3 The AfCFTA is also expected to facilitate a better integration of the African economy into the global market, thus contributing to sustainable economic growth, poverty reduction, enhanced foreign direct investment and employment creation in Africa. It is also considered to be a steppingstone towards two of the deeper integration stages envisaged in the Abuja Treaty of 1991, namely the creation of a continental customs union by 2019 and an African Economic Community (AEC) by 20284 . The AfCFTA can however pose some challenges to the signatory countries as through trade liberalization, domestic markets will become open to foreign competition and susceptible to anti-competitive practices originating outside their national borders. These include crossborder competition concerns, international cartels, mergers and acquisitions that risk monopolizing or creating abuse of dominance in the internal market5 . Some firms may gain market power and abuse their dominance through taking advantage of the economies of scale. Hence the need for the member countries, not only to dismantle trade barriers but also to adopt complementary competition policy to ensure a smooth transition and to benefit from gaining access to new markets. As was stated by Ernst-Ulrich Petersmann, competition laws are important to the preservation of economic freedom and the free trade system as is with the Bill of Rights to the protection of fundamental freedoms6 . The competition and trade policies are both based on the conviction that free trade is a means of maximizing the economic welfare of trading nations through the efficient allocation of resources. The two policies therefore complement each other as without competition, the African Continental Free Trade Area lacks legitimacy because private restraints to trade will undermine its achievement. Hence the negotiations on competition which are supposed to take place beginning of 2019 by the African Union countries who have signed the African Continental Free Trade Area. The research will therefore discuss the formation of the African Continental Free Trade Area, discuss the relationship between trade and competition and will also scrutinize the likely positive and negative impacts of the African Continental Free Trade Area vis a vis competition. Reference will also be made to other regional agreements on competition linked with regional efforts to set up free trade zones, particularly, the European Union where regional integration has been used to enhance economic growth and the useful lessons that can be learnt from those.